Adaptive coordinated control for an under-actuated airplane–tractor system with parameter uncertainties - Pengjie Xu; Weining Huang; Tianrui Zhao; Wei Zhang; Tongwei Lu; Guiyan Qiang; Lin Zhang; Yanzheng Zhao (Engineering Science and Technology, an International Journal)
The coupled system composed of an airplane and a tractor has complex dynamical and highly under-actuated characteristics. In this study, to achieve coordinated motion of the airplane–tractor system with heavy load, a novel adaptive coordinated motion controller is proposed for the system to track a desired trajectory, ensuring both the transient and steady-state performance of the system during operation. First, the dynamic model of the system is established based on Lagrangian method. A decoupling control approach for velocity and angle control is adopted based on the analysis of system dynamics. Second, a function reflecting global coordination is constructed, and then it is transformed into an unconstrained variable through a designed performance function. Next, an adaptive control structure is introduced to handle system parameters uncertainties via the unconstrained variable. Co-simulations and a real experiment are conducted in the end. Model accuracy and controller effectiveness are validated by comparing with other methods, the robustness of the proposed method are validated under different conditions in both simulation and real-world environment.